Design, Simulation, and Analysis of Micro/Nanoelectromechanical System Rotational Devices. (9th November 2021) - Kalaiarasi, A. R.; Deepa, T.; Angalaeswari, S.; Subbulekshmi, D.; Kathiravan, Raja
Abstract : This work is focused on design and simulation of microelectromechanical system (MEMS)/nanoelectromechanical system (NEMS) rotational devices such as micro/nanothermal rotary actuator and micro/nanogear. MEMS/NEMS technologies have allowed the development of advanced miniaturized rotational devices. MEMS/NEMS-based thermal actuator is a scaled version of movable device which will produce amplified motion when it is subjected to thermal forces. One of the applications of such thermal micro/nanoactuator is integrating it into micro/nanomotor that makes a thermal actuated micro/nanomotor. In this work, design and simulation of micro/nanothermal rotary actuator are done using MEMS/NEMS technology. Stress, current density, and temperature analysis are done for microthermal rotary actuator. The performance of the device is observed by varying the dimensions and materials such as silicon and polysilicon. Stress analysis is used to calculate the yield strength of the material. Current density is used to calculate the safer limit of the material. Temperature analysis is used to calculate the melting point of the material. Also, in this work, design and simulation of microgear have been done. Micro/nanogears are devices that can be used to improve motion performance. The essential is that it transmits rotational motion to a different axis.